Connections and Tensions Between University and School Districts: Research Review Boards and School-Based Research - Tilley, Susan A.; Killins, Janet; Van Oosten, Deborah (Alberta Journal of Educational Research, 2005)
Currently researchers connected to university contexts who conduct research involving human participants must receive approval from a research ethics board, and in the case of school-based research, from school district authorities. This article focuses on the ethics review of school-based research. Applications submitted to a research ethics board and a district research review committee serve as primary data for the study. Information presented relates to research interests, researchers’ background, methodologies proposed, and board decisions. Emergent themes discussed are limited to two: a focus on student researchers and research ethics review, and the connections between the research review boards and their influence on school-based research.